E. B. White correspondence - White, E. B. (Elwyn Brooks), 1899-1985.
TLS (North Brooklin, Maine) from White to Mr. Robinson concerning pronunciations and colloquialisms found in rural Maine.
Author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Colloquial language; English language -- Spoken English -- Maine; Authors